Evaluation of the recombinant antigens B2t and 2B2t, compared with hydatid fluid, in IgG-ELISA and immunostrips for the diagnosis and follow up of CE patients. - Ana Hernández-González; Carlos Sánchez-Ovejero; Raúl Manzano-Román; María González Sánchez; José Manuel Delgado; Teresa Pardo-García; Francisco Soriano-Gálvez; Okan Akhan; Carmen M Cretu; Kamenna Vutova; Francesca Tamarozzi; Mara Mariconti; et al. (Public Library of Science (PLoS), 2018)
Cystic echinococcosis (CE) is one of the most widespread helminthic zoonoses and is caused by the tapeworm Echinococcus granulosus complex. CE diagnosis and monitoring primarily rely on imaging techniques, complemented by serology. This is usually approached by the detection of IgG antibodies against hydatid fluid (HF), but the use of this heterogeneous antigenic mixture results in a variable percentage of false positive and negative results, and has shown to be useless for follow-up due to the long persistence of anti-HF antibodies in cured patients. To improve test performances and standardization, a number of recombinant antigens mainly derived from HF have been described, among them the B2t and 2B2t antigens. The performance of these antigens in the diagnosis and follow up of patients with CE has been so far evaluated on a limited number of samples. Here, we evaluated the performances of tests based on B2t and 2B2t recombinant antigens compared to HF in IgG-ELISA and immunochromatography (IC) for the diagnosis and follow-up of patients with CE in a retrospective cohort study. A total of 721 serum samples were collected: 587 from 253 patients with CE diagnosed by ultrasonography (US), 42 from patients with alveolar echinococcosis and 92 from healthy donors from Salamanca (Spain). The highest overall sensitivity was obtained with HF in ELISA (85.5%), followed by IC containing HF and 2B2t-HF (83.0% and 78.2%, respectively). The lowest sensitivity was obtained with B2t and 2B2t in ELISA (51.8%). The highest specificity was obtained with IC containing 2B2t-HF (100%), and the lowest with HF-ELISA (78.0%). The lowest cross-reactivity with sera from patients with alveolar echinococcosis was detected with the recombinant antigens in ELISA (9.5% - 16.7%) and the highest with the HF-IC (64.3%). The results of B2t and 2B2t-ELISA were influenced by cyst stage, as classified by US according to the WHO-Informal Working Group on Echinococcosis (WHO-IWGE), with low sensitivity for inactive (CE4 and CE5) cysts, and by the drug treatment, with higher sensitivity in patients after drug treatment compared with patients not subjected to drug treatment. The two recombinant antigens in ELISA provided promising results for monitoring patients in follow-up, although their use is limited to patients with positive serology against them at the beginning of the follow-up. Potential biological reasons behind the low sensitivity of the recombinant antigens and possible strategies to enhance the performance of CE serology are discussed.